Application of probabilistic modelling to food chemical exposure assessments - Gilsenan, Mary B. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2004)
Risk assessment of food chemical intake is at the core of food safety policy within the EU and the assessment of food chemical exposure is an integral part of the risk assessment process. There is an increasing demand to improve current methods to assess food chemical exposure. The research presented in this thesis demonstrates the usefulness of a National Food Ingredient Database within the exposure assessment process and focuses thereafter on the application of probabilistic modelling to food chemical exposure assessments.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin